ANTIMICROBIAL ACTIVITY AND CYTOTOXICITY OF PTEROCARPUS ANGOLENSIS EXTRACTS AND COMPOUNDS AGAINST SELECTED BACTERIAL ORGANISMS AND ENTAMOEBA HISTOLYTICA - Samie, Amidou (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Pterocarpus angolensis also known as the bloodwood tree or Mutondo in Shi-Venda is well known to traditional doctors in the Venda region and commonly used. In the present study, extracts and compounds isolated from P. angolensis were prepared and tested against different bacterial organisms and Entamoeba histolytica. The cytotoxicity of the compounds was also determined using the MTT assay. The acetone extract was the most active against all the bacterial organisms tested with MIC varying between 0.0156 mg/ml against Staphylococcus aureus and 2 mg/ml against Enterobacter cloacae. Seven pure compounds were isolated and the structures of 5 were determined. The 5 isolated compounds included Phthalate and 4 derivatives of epicatechin. All the purified compounds were active against S. aureus as determined by bio-autography. Piperitenone (a compound isolated from Lippia javanica essential oil) and one compound out the eight obtained from P. angolensis appeared to be active against E. histolytica with IC50 of 25 ìg/ml and 100 ìg/ml respectively. The other P. angolensis compounds were not active up to the concentration of 400 ìg/ml tested. The compounds isolated from P. angolensis were more toxic than Piperitenone and their IC50 was found to be between 175 ìg/ml and 375 ìg/ml. In conclusion, the present study has demonstrated the presence of epichatechin and its derivatives from the stem bark of Pterocarpus angolensis and demonstrated their weak activities against E. histolytica. Further studies are needed to characterize the activity of the isolated compounds in the treatment of other diseases.